Sweet Flavor Formulation of Agarwood Leaf Extract Powder - NAZIM, UMI UMAIRAH; A.TALIP, BALKIS (Enhanced Knowledge in Sciences and Technology, 2024)
Agarwood leaves powder is not very popular because of its strong flavor, which some people may find overpowering or strange. However, agarwood leaves are widely used in tea production. Thus, this study aim to develop new products from agarwood leaves which is sweet flavor of agarwood leave extract powder by using different formulations. This sweet flavor of agarwood leave extract powder can be used as sweet seasoning powder for food like pastry and chips. To bring out the sweet flavor of agarwood leave, the sweetener was mixed with agarwood leaf extract powder. Three formulations were created to know the suitable taste in order to enhance the sweet flavor of agarwood leaf extract powder. Formulation 1 consists of 47.51% of agarwood leave extract powder, 35.63% of stevia and 16.86% of sodium benzoate, formulation 2 consists of 47.51% of agarwood leave extract powder, 35.63% of white sugar and 16.86% of sodium benzoate while formulation 3 consists of 47.51% of agarwood leave extract powder, 35.63% of brown sugar and 16.86% of sodium benzoate. 7-point hedonic test and descriptive test were carried out to identify consumer’s acceptance and sweet flavor of agarwood leave extract powder’s sensory profiling through sensory evaluation. The ANOVA test on sensory results showed that most of sensory attributes for three formulations of sweet flavor of agarwood leave extract powder were significantly different (p<0.05). From the sensory test, formulation 2 was the most acceptable formulation with 5.93±2.15